Ectopic expression of SOX18 in Basal cell carcinoma negatively regulates tumour progression. Issue 3 (June 2020) - Villani, Rehan; Sim, Seen Ling; Roy, Edwige; Wainwright, Brandon; Francois, Mathias; Khosrotehrani, Kiarash
Highlights: Well-defined murine model of Basal Cell Carcinoma with epidermal specific Patched1 mutation. Expression of Sox18 (and SoxF factors) in the epithelial component of murine Basal Cell Carcinoma. Sox18 loss of function mutation dramatically increased Basal Cell Carcinoma progression. Sox18 may function in Basal Cell Carcinoma by mediating the interaction between Hedgehog and Notch signaling. Abstract: Background: Basal Cell Carcinoma is the most common tumour and yet much remains to be determined regarding the molecular mechanisms that leads to its development. Hedgehog signal activation is sufficient for BCC induction, but the molecular mediators of BCC growth are not well understood. SoxF transcription factor Sox18 has been identified in human BCC, but its role in growth of the tumour is as yet unknown. Objective: To determine if Sox18 is involved in the regulation of Basal Cell Carcinoma growth. Methods: We analysed the function of Sox18 by combining a dominant negative Sox18 mouse model, Sox18 +/OP with murine BCC Results: We determine that Sox18 is ectopically expressed in the epidermal cells of a murine model of Basal Cell Carcinoma. We then show that dominant negative mutation of Sox18 increases the severity of murine Basal Cell Carcinoma. Finally, decreased Hey1 in Sox18 +/OP BCC suggests Sox18 may negatively regulate BCC progression via Notch signaling. Conclusions: These data suggest that Sox18 is a hedgehog regulated mediator of tumour suppression within Basal Cell Carcinoma epidermis.